The invisible island - Roy, Ron, 1940-; Gurney, John Steven, 1962- (New York : Random House, 1999)
While picnicking on Squaw Island, Dink, Josh, and Ruth Rose find a hundred dollar bill, and when they return to explore further they find an entire cave full of money.
"A Stepping Stone book."
"Grades 2-4"--cover p. [4].
Keywords: Islands -- Fiction; Counterfeits and counterfeiting -- Fiction; Mystery and detective stories